A Cross-Sectional Study on the Epidemiology of Urinary Tract Infection in Children and its Associated Risk Factors - Tufail Hussain Tahir, Taj Muhammad, Farman Ullah, Rida Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary tract infection (UTI) is one of the most challenging and un-noticed infections in children, due to the migration of microbial flora from the fecal material to the urethra via perineum. Objectives: The study aimed to determine the incidence of UTI in children and their associated risk factors. Study Design: 362 patients were investigated and classified according to their age and gender. Methodology: Pediatric patients' urine samples were collected for urinalysis and urine culture for the confirmation of UTI. Place and Duration: This retrospective cross-sectional study was conducted at DHQ Teaching Hospital, Dera Ismail Khan, in 2020-21 and 2021-22. Results: Positive results were observed in 31 of 362 samples (10.22%); prevalence was higher among female children (12.39%) than males (6.25%). There was a statistically significant difference (P<0.05) across three age groups, infants being the most susceptible (14.90%), followed by children aged 1-5 years (7.08%) and 5-10 years (5.40%). Conclusion: Considering the high frequency of UTI in children and the difficulty in its diagnosis, due to the lack of specific symptoms, the study recommended that all pediatric patients with fever without obvious cause, the only clinical indicator, should be evaluated for UTI. Keywords: Dysurea; Pyrexia; Uncircumcised boys; Urosepsis